The Meaning of Kaffah in the Qur'an (Comparative Study of the Interpretation of Ibn Kathir in the Book of Tafsir Al-Qur'an Al-'Adhim and Wahbah Al-Zuhaili in the Book of Tafsir Al-Munir of Surah Al-Baqarah Verse 208) - Mohammad Fattah; Nabilatul Wafa (Values: Jurnal Kajian Islam Multidisiplin, 2025)
In discussing the word kaffah in the Al-Qur'an, it is only found in one verse, the meaning is "whole", which is only found in Surah Al-Baqarah verse 208, as for the problem that will be discussed in this research, it is how all humans can understand that the existence of Allah SWT and the Messengers and being able to know that all the blessings received by humans are from the power of Allah SWT. So the background of this research is so that humans know the Oneness of Allah SWT. And that only Islam is the truest religion, namely the Islamic religion that was conveyed by the Prophet Muhammad to all mankind. This research uses a library method, namely reviewing data and sources in this research by taking references from several books and journals related to the meaning of kaffah. The interpretive method used by the mufassir in this research is very different, such as Ibn Katsir's interpretation in the book Tafsir Al-Qur'an Al-'Adhim is a Muqarran (comparative) interpretation, while Wahbah Al-Zuhaili's interpretation in the book Tafsir Al-Munir is a Tahilili (examining) interpretation. Verse by verse and letter by letter according to the order in the Qur'an). The results of this research are so that readers can know and understand and spread the religion of Islam and become part of Islam as a whole without exception or only half of it. As for Ibn Kathir's opinion in the Tafsir Al-Qur'an Al-'Adhim, the meaning of kaffah is "whole", in embracing Islam because in this verse Allah SWT. Ordered all his ummah to embrace Islam as a whole without exception. Wahbah Al-Zuhaili's opinion in the Book of Tafsir Al-Munir means kaffah is "whole", namely that humans as a whole convert to Islam and not just partially or half-heartedly and apply the teachings of the Islamic religion in everyday life and practice them with other humans.